Emissão de amônia e dinâmica do nitrogênio no solo com parcelamento da dose e adição de inibidor de nitrificação em dejetos de suínos - Pujol, Stefen Barbosa (2012)
Pig Slurry (PS) is used mainly as a fertilizer for crops in southern Brazil where the predominant soil management is in no-tillage. Thus, the application of manure on the soil surface can increase losses of nitrogen (N) for volatilization of ammonia (NH3), leading to reduction in the fertilizing potential of waste and increased environmental pollution. Moreover, as the PS are rich in ammonium N, nitrification can occur quickly and easily and the generated nitrate can also be lost by leaching and denitrification. Then, it is necessary to look for alternatives to mitigate these losses of N fertilizer and maximize the potential of the PS. One of the possibilities to enable greater efficiency and lower pig slurry pollution potential is to perform the application in the soil in split doses, while other strategy is the use of nitrification inhibitors (NI). Thus, the amount of ammonium N applied to the soil surface would be divided into smaller fractions rather than a single application, minimizing the losses by NH3 volatilization and with the delay in the appearance of nitrate (NO3 -) the transfer of this anion to lower soil layers. To evaluate these aspects, experiments were conducted in an Ultisol in no-tillage handled in the agricultural year of 2010/2011, on the campus of Universidade Federal de Santa Maria (UFSM). The treatments were arranged in randomized blocks and evaluated in maize, summer of 2010/2011, and wheat, winter of 2011, consisting the application of PS in a single dose (pre-sowing) and split doses (1/3 in pre-sowing and 2/3 in coverage), with and without the use of nitrification inhibitor dicyandiamide (DCD), present in the product Agrotain® Plus (81 % of DCD) and applied at 7.0 kg ha-1. Besides, a treatment with recommended dose of urea N for both cultures and a control treatment without the use of fertilizer were evaluated. Volatilized NH3 was captured inside the semi-open static chambers containing sponge soaked with a mixture of phosphoric acid and glycerin. Soil samples were collected one day after experiments were set up, and on subsequent days to allow the detection of the changes of inorganic N in soil during the development of both cultures. These samples were analyzed for ammonium N and nitrate N according to Tedesco et al. (1995). The nitrification inhibitor (DCD) maintained N of manure applied to the soil in ammonium form without increasing the emission of NH3 to atmosphere, while the application of PS in parts or not did not differ in the amount of volatilized NH3 and in the percolation of nitrate in the soil.